﻿Pecking Order Theory, Trade-Off Theory and Determinants of Capital Structure: Empirical Evidence from Malaysia - Lim, Anthony, Chuen Eu (2011)
This study focuses on the relevance of the classical capital structure theories of the pecking order and the trade-off model in providing general explanation of the financial behaviour of Malaysian firms from 2002 to 2010. The theoretical framework suggested the potential of exhibiting asymmetrical financing behaviour for firms with leverage above and below the target leverage level with its financial surplus and deficit. With past empirical studies focused more on the determinants of capital structure, and whether the firms follow the pecking order or trade-off theory, little has be done on the examination of the variety of pecking order and trade-off asymmetric models, along with comparing their performance against the symmetric alternative.